2001
DOI: 10.1590/s0100-879x2001000400001
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding: a perspective for biology, medicine and biotechnology

Abstract: At the present time, protein folding is an extremely active field of research including aspects of biology, chemistry, biochemistry, computer science and physics. The fundamental principles have practical applications in the exploitation of the advances in genome research, in the understanding of different pathologies and in the design of novel proteins with special functions. Although the detailed mechanisms of folding are not completely known, significant advances have been made in the understanding of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 60 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Molecular chaperones function to restrain denatured proteins from aggregation and/or to assist protein folding (Barral et al, 2004;Hartl and Hayer-Hartl, 2002;Yon, 2001;Young et al, 2004). In this study, we used Taq DNA polymerase, an important enzyme in biotechnology (Dalton, 1999(Dalton, , 2001Pavlov et al, 2004), as a model substrate for examining the effects of chaperones on stability and durability of Taq polymerase, by incorporating chaperones into PCR reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular chaperones function to restrain denatured proteins from aggregation and/or to assist protein folding (Barral et al, 2004;Hartl and Hayer-Hartl, 2002;Yon, 2001;Young et al, 2004). In this study, we used Taq DNA polymerase, an important enzyme in biotechnology (Dalton, 1999(Dalton, , 2001Pavlov et al, 2004), as a model substrate for examining the effects of chaperones on stability and durability of Taq polymerase, by incorporating chaperones into PCR reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular chaperones or other stress responsive proteins would play important roles in cell tolerance, which can restrain denatured proteins from aggregation and/or assist protein folding (Hartl and HayerHartl 2002;Barral et al 2004;Yon 2001;Young et al 2004). Previous studies showed that the addition of chemical chaperones (TMAO) could promote E. coli growth at elevated temperature, even up to 46°C (Gur et al 2002;Derlinden et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ow proteins fold into functional, three-dimensional structures has been under intense study (1), and the folding pathways for a number of eukaryotic proteins have been characterized in vitro (2,3) or in vivo (4)(5)(6)(7)(8)(9). In the secretory pathway, protein folding is coupled to the formation and reshuffling of disulfide bonds.…”
mentioning
confidence: 99%